Characterization of the Exonic Regions of the JY‐1 Gene in Zebu Cattle and Buffaloes. Issue 6 (29th May 2013) - de Camargo, GMF; Baldi, F; Regitano, LCA; Tonhati, H
Contents: Protein JY‐1 is an oocyte‐specific protein that plays an important regulatory role in the granulosa cell layer and during the early embryo development stages. It is the first specific protein of maternal origin discovered in a single‐ovulating species. In this study, the exon regions of the JY‐1 gene were characterized by sequencing in 20 unrelated cattle ( Bos taurus indicus ) and 20 unrelated buffaloes ( Bubalus bubalis ). Eighteen polymorphisms were detected in cattle and 10 polymorphisms in buffaloes. Some of the polymorphisms were identified in codifying regions and caused amino acid changes. The insertion of a thymine was detected in the codifying region of exon 3 of the buffalo sequence when compared to the cattle one. This insertion causes a change in the codons frameshift from this point onwards, modifying the 19 terminal amino acids of the buffalo protein and creating a premature stop codon. This finding may explain reproductive differences between cattle and buffaloes in terms of follicle recruitment, embryo development and incidence of twin pregnancies.